THE USE OF FIGURATIVE LANGUAGE IN KATY PERRY SONG - Sri Arfani; Sri Chandra Damayanti (STIBA IEC JAKARTA, 2019)
The objective of this research is to analyze slang words in Top Five movie. Learning slang is important for people who want to fully understand English either it is formal or informal. The movie is analyzed using the descriptive qualitative method. The data were collected through library and internet research then watch the movie several times. The first analysis of the research is about slang words that used in the movie. The second analysis is about forms of slang that found in the movie. Then the third analysis is about functions of slang words used in the movie. The result of this research indicated that: (1) There are ten slang words that are going to discuss in this research, (2) There are eleven forms of slang that found in the movie; compounding, affixation, phraseology, clipping, initialism, verbification, nominalization, other process, blending, (3) There are nine functions of slang that used in the movie; identification, interaction, secrecy, emotions, humor, toughness, informality, conciseness, and forcefulness.